2018
DOI: 10.1371/journal.pgen.1007654
|View full text |Cite
|
Sign up to set email alerts
|

Polynucleotide phosphorylase: Not merely an RNase but a pivotal post-transcriptional regulator

Abstract: Almost 60 years ago, Severo Ochoa was awarded the Nobel Prize in Physiology or Medicine for his discovery of the enzymatic synthesis of RNA by polynucleotide phosphorylase (PNPase). Although this discovery provided an important tool for deciphering the genetic code, subsequent work revealed that the predominant function of PNPase in bacteria and eukaryotes is catalyzing the reverse reaction, i.e., the release of ribonucleotides from RNA. PNPase has a crucial role in RNA metabolism in bacteria and eukaryotes ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 136 publications
(158 reference statements)
1
37
0
Order By: Relevance
“…We have reconstituted in vitro the protective target trimming by Cbf1 and confirmed that, as in the original observations with B. subtilis YhaM (Oussenko et al , ; Fang et al , ), this reaction is Mn 2+ ‐dependent (Fig A). Intriguingly, Cbf1 is the first 3′→5′ exonuclease in Gram‐positive bacteria with a protective effect on sRNAs, and the second when PNPase‐mediated stabilization of some Hfq‐dependent sRNAs in E. coli is counted (Cameron et al , , ). This protection is also reminiscent of certain eukaryotic ncRNAs, which can be trimmed at their 3′ ends by PARN and TOE1, leading to enhanced stability (Berndt et al , ; Tseng et al , ; Son et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…We have reconstituted in vitro the protective target trimming by Cbf1 and confirmed that, as in the original observations with B. subtilis YhaM (Oussenko et al , ; Fang et al , ), this reaction is Mn 2+ ‐dependent (Fig A). Intriguingly, Cbf1 is the first 3′→5′ exonuclease in Gram‐positive bacteria with a protective effect on sRNAs, and the second when PNPase‐mediated stabilization of some Hfq‐dependent sRNAs in E. coli is counted (Cameron et al , , ). This protection is also reminiscent of certain eukaryotic ncRNAs, which can be trimmed at their 3′ ends by PARN and TOE1, leading to enhanced stability (Berndt et al , ; Tseng et al , ; Son et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…PNPase is a processive exonuclease that degrades RNA and DNA in the 3’−5’ direction, and also catalyzes the reverse reaction in which nucleotide diphosphates are added back onto the 3’-end of the substrate (Cameron et al, 2018; Cardenas et al, 2009; Walker et al, 2017). Our previous work showed that in a purified system, Csm5 can bind to PNPase and stimulate its nucleolytic activity while repressing its polymerization function (Walker et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, our previous work showed that the Cas10-Csm complex, when expressed in its native S. epidermidis host, co-purifies with several cellular nucleases in trace amounts (Walker et al, 2017). Furthermore, in a reconstituted system, Csm5 can bind and stimulate one of these nucleases, PNPase (polynucleotide phosphorylase), a highly-conserved enzyme that is responsible for the processing and degradation of cellular RNAs in bacteria and eukaryotes (Cameron et al, 2018). This observation lead us to propose a model wherein PNPase and other non-Cas nucleases are likely responsible for crRNA maturation (Walker et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, I have also added two new enzymes that could have played a fundamental role in the prebiotic world and that have been preserved to this day: polynucleotide phosphorylase (PNPase) and non-ribosomal peptide synthetases (NRPS). PNPase is an evolutionary conserved bifunctional enzyme with a phosphorolytic exonuclease activity and the capacity of synthesizing RNA using any ribonucleoside diphosphate [42]. PNPase synthesizes RNA without any of the components involved in transcription and for this reason, I call this as non-transcriptional RNA synthesis.…”
Section: The Reformulated Central Dogmamentioning
confidence: 99%